Evaluating the accessibility and equity of key amenities in the X-minute and Y-monetary-cost city: A double-threshold cumulative opportunity measure - Yue Chen; Shunping Jia; Qi Xu (Journal of Public Transportation)
Accessibility is essential for the equitable planning of key amenities such as job, healthcare, and education in the X-minute city. However, previous studies tend to ignore the monetary cost of travel in accessibility modelling or fail to provide an effective accessibility planning tool based on the monetary cost. To fill the gap, this paper proposes a double threshold cumulative opportunity measure considering the travel time and monetary cost and applies it in the accessibility and equity evaluation of six amenities by public transportation (PT) and private car (PC) in the X-minute and Y-monetary-cost city. The effects of the monetary cost on accessibility and equity are fully explored. And the proposed method is compared with traditional accessibility models to show its advantages. The results from two typical combinations of thresholds show that the accessibility of all amenities by PT is still much lower than that of PC. It also presents a more uneven spatial distribution, originating from the accessibility gap in different housing areas. Among different amenities, education and scenery are the most inequitably distributed. Moreover, the incorporation of the travel cost threshold is needed in modelling as the traditional method will overestimate the accessibility and have contrary effects on the equity of PT and PC. Compared with existing methods, the double-threshold cumulative opportunity measure has better simplicity and interpretability. And the new model is more general as the traditional method can be viewed as a special form of it. This study provides insights for planners and policymakers to make targeted adjustments to resource allocation and transportation policies in future transportation and urban planning in the X-minute and Y-monetary-cost city.